Simultaneous EEG and fMRI at high fields - Mullinger, Karen Julia (2008)
The work described in this thesis involves an investigation of the implementation and application of simultaneous EEG and fMRI. The two techniques arc complementary, with EEG providing excellent temporal resolution and fMRI having good spatial resolution. Combined EEG/fMRI thus forms a powerful tool for neuroscience studies. In initial work, methods for improving the removal of the gradient and pulse artefacts, which are induced in EEG traces recorded during concurrent MRI, have been developed. Subsequently, the effects of the EEG hardware on MR images were investigated. This involved acquiring a series of scans to identify the sources of B0- and B1 inhomogeneities and the extent to which these affect EPI data. The adverse effects on data quality of combining EEG and fMRI increase with field strength. Consequently, EEG-fMRI at 7T is particularly challenging, although a number of advantages make its implementation desirable. Safety tests were performed which showed the presence of the EEG system caused a negligible increase in RF heating effects during scanning at 7T. After elimination of a number of noise sources, the first simultaneous EEG-fMRI experiments at 7T using commercially available equipment were performed. Concurrent EEG/fMRI at 3T was then used to investigate the correlation between the BOLD (blood oxygenation level dependent) response measured during visual stimulation and both the preceding alpha power and the strength of the driven, electrical response. In considering the correlation of the range of variation of the alpha power and BOLD response, a trend emerged which allowed tentative conclusions to be drawn. Variation of the BOLD and driven response with the frequency of visual stimulation relative to a subject's individual alpha frequency (IAF) was also investigated. A significant increase in the driven response, accompanied by a decrease in the BOLD response was observed in visual cortex when it was driven at the IAF.